Kompetensi Dasar Perawat Baru Sebelum dan Sesudah Pelatihan Metode Preceptorship di Rumah Sakit Sumber Waras Jakarta - Esther Lenny Dorlan Marisi; Imam Makhrus; Sudibyo Supardi (FORIKES, 2021)
Increasing the core competence of newnurses can be achieved with the correct preceptorship method. This research aims to determine the increase of core competencies of new nurses after the preceptorship method training. This research was a quasi experimental design with the type of one group pre-post test. Sampling was done using purposive sampling technique, namely 33 new nurses with a service period of less than 1 year. The intervention in this research was to provide preceptorship training for 21 preceptors. Comparison of the mentoring between preceptors and perceptees 1: 2. The data collection was carried out before and 4 weeks after the training. The data collection tool used a questionnaire with a nominal scale. Data analysis used the Chi-Square test, Wilcoxon test and logistic regression test. The majority of the characteristics of new nurses who were competent to their core competencies of 69.7%, there were differences core competence increasing on average of 39.03% and statistically significant (p-value = 0.000), increasing the core competence of new nurses was also influenced by education. The group at age 17-5 years old, D3 nursing education and good self-efficacy have a significant relationship with increasing the core competence of nurses. New nurses with D3 nursing education have the likehood of their core competence increasing 28.29 times after preceptorship training for preceptors compared to nurse with undergraduate nursing education, which controlled by the PO fit variable. Keywords: preceptorship; basic competencies; new nurses ABSTRAK Peningkatan kompetensi dasar perawat baru dapat dicapai dengan metode preceptorship yang dilakukan secara benar. Penelitian ini bertujuan untuk mengetahui peningkatan capaian kompetensi dasar perawat baru sesudah dilakukan pelatihan metode preceptorship. Penelitian ini menggunakan desain quasi experiment jenis one group pre-post test. Pencuplikan sampel dilakukan dengan teknik purposive sampling yakni perawat baru dengan masa kerja kurang dari 1 tahun sebanyak 33 orang. Intervensi dalam penelitian ini dengan memberikan pelatihan preceptorship terhadap 21 preceptor. Perbandingan pendampingan antara preceptor dengan preceptee 1:2. Pengumpulan data dilakukan sebelum dan 4 minggu setelah dilakukan pelatihan. Alat pengumpulan data menggunakan kuesioner dengan skala nominal. Analisis data menggunakan uji Chi-Square, uji Wilcoxon dan uji regresi logistik. Hasil penelitian ini; diidentifikasi mayoritas karakteristik perawat baru yang kompeten terhadap kompetensi dasarnya sebesar 69,7%, terdapat perbedaan kompetensi dasar perawat baru sesudah pelatihan preceptorship yakni terjadi peningkatan kompetensi rata-rata 39,03% dan secara statistik bermakna (p value = 0,000), peningkatan kompetensi dasar perawat baru juga dipengaruhi oleh pendidikan. Kelompok umur 17-25 tahun, pendidikan D3 keperawatan dan self efficacy baik berhubungan bermakna dengan peningkatan kompetensi dasar perawat. Perawat baru dengan pendidikan D3 keperawatan mempunyai kemungkinan kompetensi dasarnya meningkat 28,29 kali setelah pelatihan preceptorship terhadap preceptor dibandingkan perawat dengan pendidikan sarjana keperawatan ners, dikontrol oleh variabel PO Fit. Kata kunci: preceptorship; kompetensi dasar; perawat baru